Hamstrings strength imbalance in professional football (soccer) players in Australia - Ardern, C. L.; Pizzari, T.; Wollin, M. R.; Webster, K. E. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study was to describe the isokinetic thigh muscle strength profile of professional male football players in Australia. Concentric (60° and 240°/s) and eccentric (30° and 120°/s) hamstrings and quadriceps isokinetic strength was measured with a HUMAC NORM dynamometer. The primary variables were bilateral concentric and eccentric hamstring and quadriceps peak torque ratios, concentric hamstring-quadriceps peak torque ratios, and mixed ratios (eccentric hamstring 30°/s ÷ concentric quadriceps 240°/s). Hamstring strength imbalance was defined as deficits in any 2 of: bilateral concentric hamstring peak torque ratio <0.86, bilateral eccentric hamstring peak torque ratio <0.86, concentric hamstring-quadriceps ratio <0.47, and mixed ratio <0.80. Fifty-five strength tests involving 42 players were conducted. Ten players (24%) were identified as having hamstring strength imbalance. Athletes with strength imbalance had significantly reduced concentric and eccentric bilateral hamstring peak torque ratios at all angular velocities tested; and reduced eccentric quadriceps peak torque (30°/s) in their stance leg, compared with those without strength imbalance. Approximately, 1 in 4 players had preseason hamstring strength imbalance; and all strength deficits were observed in the stance leg. Concentric and eccentric hamstrings strength imbalance may impact in-season football performance and could have implications for the future risk of injury.